Extract Potential Gotu Kola Leaf (Centella Asiatica L.) In Accelerating Burn Wound Healing - Hardaningtyas, Kishanty (Sean Institute, 2024)
This study aims to evaluate the effectiveness of gotu kola leaf extract in accelerating the healing of burn wounds. Through a literature review of ten studies between 2014 and 2024, the authors collected data from accredited and indexed scientific journals. The results show that gotu kola leaf extract has great potential in accelerating burn wound healing, both in in vivo and in vitro models. The analysis highlighted significant improvements in tissue regeneration, reduced inflammation, and antibacterial activity against Staphylococcus aureus. A literature review is the author's approach in evaluating the effectiveness of gotu kola leaf extract. Data was taken from ten studies published in accredited and indexed scientific journals between 2014 and 2024. The author used descriptive analysis methods to present the findings from the selected studies. The findings show that gotu kola leaf extract has a positive effect in accelerating the healing of burn wounds. Various extract formulations, such as gels, creams, compresses, ointments, and infusions, have been proven to be effective in reducing inflammation, increasing vascularization, stimulating tissue regeneration, and inhibiting the growth of bacteria, especially Staphylococcus aureus. This research provides important insights into the effectiveness of gotu kola leaf extract in the treatment of burns. With various formulations and methods of use, gotu kola leaf extract has been proven to be effective in speeding up the healing process and reducing the risk of infection. However, further research is needed, especially in human clinical trials, to validate these findings in more depth. In conclusion, gotu kola leaf extract offers an attractive and natural alternative in the treatment of burns, with the potential to become an important part of comprehensive therapy in burn wound management.